2001
DOI: 10.1148/radiology.218.1.r01dc1155
|View full text |Cite
|
Sign up to set email alerts
|

Hepatic Metastases from Colorectal Cancer: Preoperative Detection and Assessment of Resectability with Helical CT

Abstract: Helical CT is a noninvasive, reliable, and accurate technique for imaging the liver and should be considered as the standard preoperative work-up of hepatic metastases from colorectal cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
89
0
9

Year Published

2008
2008
2012
2012

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 233 publications
(104 citation statements)
references
References 23 publications
6
89
0
9
Order By: Relevance
“…In terms of the cumulative rate of recurrence in situ, the KaplanMeier curve in our study appeared identical to or slightly more favorable than that reported in two previous studies (8,9) CT appears to be the most commonly used imaging modality in the evaluation of the effect of chemotherapy according to RECIST criteria (12). It has been reported that the sensitivity of helical CT is 66-84% (13)(14)(15)(16). In patients with persistent macroscopic disease at surgery, morphological changes in the structure of the liver due to chemotherapy, including steatosis, sinusoidal dilatation and fibrosis, may be responsible for underestimation of liver metastases (17).…”
Section: Discussionsupporting
confidence: 85%
“…In terms of the cumulative rate of recurrence in situ, the KaplanMeier curve in our study appeared identical to or slightly more favorable than that reported in two previous studies (8,9) CT appears to be the most commonly used imaging modality in the evaluation of the effect of chemotherapy according to RECIST criteria (12). It has been reported that the sensitivity of helical CT is 66-84% (13)(14)(15)(16). In patients with persistent macroscopic disease at surgery, morphological changes in the structure of the liver due to chemotherapy, including steatosis, sinusoidal dilatation and fibrosis, may be responsible for underestimation of liver metastases (17).…”
Section: Discussionsupporting
confidence: 85%
“…A large meta-analysis by Bipat et al [21] that included 90 studies showed similar accuracies between ultrasound, CT and MRI for the assessment of nodal involvement by rectal cancer. In a study of 137 patients, Valls et al [22] showed good accuracy (85.1%), high positive predictive value (96.1%) and low positive predictive value (3.9%) of CT for the detection of liver metastases. For the detection of CRC metastases, CT imaging in the portal venous phase is the technique of choice.…”
Section: Pre-treatment Stagingmentioning
confidence: 97%
“…CLMs are often missed at laparotomy or even preoperative diagnostic tools, including multislice contrast-enhanced computed tomography or magnetic resonance imaging, which have higher sensitivity rates for the disease [7,8]. Thus, intraoperative ultrasound (IUS) has been routinely used for detecting additional lesions which were not identified with preoperative radiological evaluations [9,10].…”
Section: Introductionmentioning
confidence: 99%